Comparison of Diagnostic Accuracy of TIMI and Grace Risk Scores for Prediction of Severity of Disease in Coronary Arteries in Non-ST-Elevation Myocardial Infarction Patients - Iftikhar Ahmad, Muhammad Saleem, Islam Shah, Naveed Hussain, Muhammad Kashif Iltaf, Qasim Rauf, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and objective: The timing of interventions in cases of non-ST segment elevation myocardial infarction (NSTEMI) is subject to risk classification. Among patients with current non-ST-elevation myocardial infarction (NSTEMI), a small research assessed two risk scores: TIMI and GRACE. Methods: Retrospective observational study of 68 patients over 4 years. Hospital admission TIMI and GRACE values were calculated. Mortality, re-infarction, heart failure, stroke, cardiac shock, and resuscitation were in-hospital endpoints. A 4-year follow-up showed all-cause and cardiac mortality. All data was analyzed using SPSS 22.0. Results: There were 42 (61.8%) males and 26 (38.2%) females with mean age 63.4 years. Most common clinical outcomes were hypertension, hyperlipidemia, diabetes, ischemia stroke and renal insufficiency. 22 (32.4%) cases were smokers. In terms of both short-term and long-term outcomes, we discovered that GRACE risk scores outperformed TIMI risk scores. Conclusion: Continuous TIMI and GRACE scores can predict NSTEMI outcomes in patients in a simple and promising way. GRACE exceeded TIMI both in-hospital and long-term outcomes. Keywords: GRACE, TIMI, NSTEMI, Outcomes